2009
DOI: 10.1080/00952990902968585
|View full text |Cite
|
Sign up to set email alerts
|

Differences in Sexual Risk Behaviors among Male and Female HIV-Seronegative Heterosexual Methamphetamine Users

Abstract: Background-Despite increased awareness and attention towards methamphetamine (MA) use among men who have sex with men (MSM), few studies have examined behaviors and effects of MA use among heterosexual populations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
34
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(37 citation statements)
references
References 19 publications
2
34
1
Order By: Relevance
“…Although yama pills are swallowed, both forms are usually melted and the vapors inhaled, resulting in rapid neurologic effects [11,12]. Use of ATS has been associated with elevated HIV risk behavior in many countries and in several population subgroups [3,9,[13][14][15][16][17][18][19]. The United Nations Office on Drugs and Crime (UNODC) reports that use of these drugs is widespread in Asia and increasing rapidly in Cambodia [20].…”
Section: Introductionmentioning
confidence: 99%
“…Although yama pills are swallowed, both forms are usually melted and the vapors inhaled, resulting in rapid neurologic effects [11,12]. Use of ATS has been associated with elevated HIV risk behavior in many countries and in several population subgroups [3,9,[13][14][15][16][17][18][19]. The United Nations Office on Drugs and Crime (UNODC) reports that use of these drugs is widespread in Asia and increasing rapidly in Cambodia [20].…”
Section: Introductionmentioning
confidence: 99%
“…Almost no studies have investigated women as perpetrators of IPV in relation to meth use. Because female meth users report greater overlap in their intimate partners and drug network, they are more likely to report initiation of meth use by an intimate partner and more likely to share meth or needles with such a partner (Cheng et al 2009). In one large treatment trial, 80% of 562 female participants with meth dependence reported abuse or violence at the hands of their partners; 40% experienced both physical and sexual abuse (Cohen et al 2003).…”
Section: Meth and Violencementioning
confidence: 99%
“…The prevalence of ATS dependence is high in women (Brecht et al, 2004). Clinical studies have demonstrated a higher prevalence of mood disorders and psychiatric disorders in female methamphetamine (MA) users (Lin et al, 2004;Cottler et al, 2005;Cheng et al, 2009). A higher rate of suicidal ideation has also been reported in females (Lin et al, 2004).…”
mentioning
confidence: 95%
“…Furthermore, it is well known that the use of MA greatly increases the risk of sexually transmitted diseases and unwanted gestation in women because it facilitates unprotected sexual behavior (German et al, 2008;Liao et al, 2011). Women usually have easy access to ATSs and prefer them because of their effects of sexual arousal and weight loss (Cohen et al, 2007;Cheng et al, 2009). It is supposed that they may suffer from poor reproductive functions because of excessive weight loss, unhealthy lifestyle, and the direct effect of the ATSs.…”
mentioning
confidence: 98%